2020
DOI: 10.1007/s40618-020-01393-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the SARS-CoV2 pandemic dissemination on the management of neuroendocrine neoplasia in Italy: a report from the Italian Association for Neuroendocrine Tumors (Itanet)

Abstract: Introduction The organization of the healthcare system has significantly changed after the recent COVID-19 outbreak, with a negative impact on the management of oncological patients. The present survey reports data collected by the Italian Association for Neuroendocrine Tumors on the management of patients with neuroendocrine neoplasia (NEN) during the pandemic dissemination. Methods A survey with 57 questions was sent to NEN-dedicated Italian centers regarding the management of patients in the period March 9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Screening for breast and colorectal cancers had decreased by 89% and 85%, respectively. An Italian survey concluded than the incidence of neuroendocrine neoplasia (NEN) decreased by 77% during the national lockdown ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Screening for breast and colorectal cancers had decreased by 89% and 85%, respectively. An Italian survey concluded than the incidence of neuroendocrine neoplasia (NEN) decreased by 77% during the national lockdown ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…From a survey focused on the management of patients with neuroendocrine neoplasms (NENs) during the pandemic (COVINET), it emerged that most of the 24 responding centres (21, 87.5%) used telemedicine for follow-up visits of these patients, which were conducted by phone, video calls, email or instant messaging ( 22 ). Operational modifications reported in the survey by Freudenberg et al included the adoption of online conferences (57%), online reporting (26%), and video consultations for patients and referring physicians (26%) ( 3 ).…”
Section: Organisational Changesmentioning
confidence: 99%
“…Panzuto et al reported that the activity of multidisciplinary teams was maintained in 19 (79.2%) of sites; however, the medium of discussion was changed in 12 centres (50%), switching from physical meetings to web-based virtual meetings. In 5 centres (20.8%), multidisciplinary team activity was suspended ( 22 ).…”
Section: Organisational Changesmentioning
confidence: 99%
“…As no one would ever have imagined, in 2020, a new pandemic undoubtedly put societies all over the world to the test. The 2020 SARS-CoV-2 outbreak and the related severe pneumonia has had a significant impact on healthcare organizations and on the general management of oncological patients that have a higher risk of infections [ 115 ]. In most countries, oncological centers remodulated access to the hospital and cancer management in order to minimize the exposure of cancer patients to the infection.…”
Section: Impact Of Covid-19 Pandemic At a Glancementioning
confidence: 99%